Gleaning: old name, new practice. Issue 2 (3rd May 2016) - Dikovic, Jovana
ABSTRACT: The practice of gleaning is linked to the centuries-old custom embedded in the customary laws of many people, according to which the master of the land holds the right to allow the poor to follow harvesters in the field and to gather and glean the fallen spears of grain. In this article, the new meaning of the practice of gleaning is analyzed by using an example of one Serbian village in Vojvodina province, Gaj, which is still predominately agricultural. In a strict sense, the name of the old practice is kept, but the essence of the practice itself and its symbolism have changed radically. In previous times, the term "gleaning" referred to the reciprocal social, economic and political relationship between the poor and the landowner. Today, in the context of the village of Gaj, it is mostly used as a euphemism for field theft. The article analyzes this gradual shift in diachronic and social-anthropological perspectives, aiming to depict and explain crucial changes in informal and formal institutions that have contributed to this current understanding of gleaning.